Universal laws for air velocities in airblast events during block caving. (January 2019) - Palma, Sergio; Galindo-Torres, S.A.; Delonca, A.; Ruest, M.; Scheuermann, A.; Finn, D.
Abstract: In this paper, we have used a simulation software to show and characterize the phenomenology associated with airblast events in 3D when the block caving method is used in underground mining. The code couples the Lattice Boltzmann Method (LBM) and the Discrete Element Method (DEM) to simulate in an realistic way the interaction between rocks and the compressed air inside the mine. An underground mine model in 3D has been implemented to quantify simultaneously the air-velocity at the drawpoints and at the observation duct, when an airblast event occurs without warning due to the sudden fall of stuck rocks. The set of numerical simulations include several combinations of the physical properties of the muckpile as the height, angle and, permeability of the fractured zone. As well as, the air-gap size and the position of the observation duct in the mine. Using scaling arguments, a novel mathematical expression formed by the Darcy number is proposed to explain the maximum velocity of the air at the drawpoints. The results presented in this paper can be applied to design hazard and risk matrices in the mining industry, and therefore mitigate the possible damages to the personnel of the mine as well as to the equipment.